2005
DOI: 10.1136/thx.2005.043695
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of ovalbumin-induced experimental allergic bronchitis in rats by inhaled inhibitor of secretory phospholipase A2

Abstract: Background: The pathophysiology of asthma involves the action of inflammatory/allergic lipid mediators formed following membrane phospholipid hydrolysis by phospholipase A 2 (PLA 2 ). Cysteinyl leukotrienes are considered potent inducers of bronchoconstriction and airway remodelling. Ovalbumin (OVA) induced bronchoconstriction in rats is associated with increased secretory PLA 2 (sPLA 2 ) activation and cysteinyl leukotriene production, together with suppression of cytosolic PLA 2 and prostaglandin E 2 . These… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
26
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(36 citation statements)
references
References 33 publications
10
26
0
Order By: Relevance
“…8,52,53 Similarly, in the study of EAB in rats, we found that the disease induction is associated with increased sPLA 2 expression and Cys-LTs production, whereas cPLA 2 expression and PGE 2 production were decreased. 11,35 This concurs with other studies that indicate that, by acting on different AA pools, sPLA 2 types were responsible for Leukotriene production, whereas PGE 2 was produced by cPLA 2 . 11,35 This indeed makes physiologic sense in airway conditions because Cys-LTs are bronchoconstrictors, whereas PGE 2 is a bronchodilator.…”
Section: Pla 2 Isoforms In Airway Pathologiessupporting
confidence: 93%
See 2 more Smart Citations
“…8,52,53 Similarly, in the study of EAB in rats, we found that the disease induction is associated with increased sPLA 2 expression and Cys-LTs production, whereas cPLA 2 expression and PGE 2 production were decreased. 11,35 This concurs with other studies that indicate that, by acting on different AA pools, sPLA 2 types were responsible for Leukotriene production, whereas PGE 2 was produced by cPLA 2 . 11,35 This indeed makes physiologic sense in airway conditions because Cys-LTs are bronchoconstrictors, whereas PGE 2 is a bronchodilator.…”
Section: Pla 2 Isoforms In Airway Pathologiessupporting
confidence: 93%
“…11,35 This concurs with other studies that indicate that, by acting on different AA pools, sPLA 2 types were responsible for Leukotriene production, whereas PGE 2 was produced by cPLA 2 . 11,35 This indeed makes physiologic sense in airway conditions because Cys-LTs are bronchoconstrictors, whereas PGE 2 is a bronchodilator. 11,35,40 However, the eicosanoids, as metabolites of AA, are downstream products of the cascade of inflammatory lipid mediators, whereas the upstream PLA 2 action produces both AA and lysophospholipids (Lyso-PL).…”
Section: Pla 2 Isoforms In Airway Pathologiessupporting
confidence: 93%
See 1 more Smart Citation
“…In a previous study, we investigated the involvement of PLA 2 s and eicosanoids in asthma pathophysiology using a rat model of ovalbumin (OVA)-induced experimental allergic bronchitis (EAB) [4], [11], as expressed by broncho-constriction, airway remodeling, the levels of the broncho-dilator PGE 2 and the broncho-constrictor Cysteinyl-LTs (CysLTs) in bronchoalveolar lavage (BAL). Upon induction of EAB these indices were up-regulated, except for PGE 2 which was markedly reduced.…”
Section: Introductionmentioning
confidence: 99%
“…7 Gene silencing of either group V or X sPLA 2 in mice with ovalbumin-induced asthma attenuates T-helper cell type 2 infl ammation. [8][9][10] We have reported that sPLA 2 stimulate mucus hypersecretion in the ferret trachea through activation of the lipoxygenase (LO) pathway. 11 Mucus obstruction of airways and goblet cell hyperplasia are characteristic of severe asthma.…”
Section: [ 1 4 7 # 6 C H E S T J U N E 2 0 1 5 ]mentioning
confidence: 99%